2014
DOI: 10.1002/jbm.b.33141
|View full text |Cite
|
Sign up to set email alerts
|

Properties of dehydrated human amnion/chorion composite grafts: Implications for wound repair and soft tissue regeneration

Abstract: PURIONV R processed dehydrated human amnion/chorion membrane (dHACM; MiMedx Group, Marietta, GA) tissue products were analyzed for the effectiveness of the PURION V R process in retaining the native composition of the amniotic membrane and preserving bioactivity in the resulting products. dHACM was analyzed for extracellular matrix (ECM) composition through histological staining and for growth factor content via multiplex ELISA arrays. Bioactivity was assessed by evaluating endogenous growth factor production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
170
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(178 citation statements)
references
References 19 publications
3
170
0
5
Order By: Relevance
“…As a nonadherent cell type, HSCs were not examined for cell migration using the Oris™ assay; however, previously published studies have shown that dHACM recruits HSCs to the site of a wound in vivo in a mouse subcutaneous implantation model 3. Over 50 soluble growth factors and cytokine proteins have been identified in soluble extracts of dHACM,32, 33 suggesting that dHACM contains soluble components that elute from the tissue and stimulate the growth and chemotactic migration of different types of stem cells, thus amplifying the number of stem cells locally. However, due to the complexity of this unique material, a causative effect cannot be assigned to any single regulatory protein or other signaling molecule either currently identified or yet to be identified in dHACM tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a nonadherent cell type, HSCs were not examined for cell migration using the Oris™ assay; however, previously published studies have shown that dHACM recruits HSCs to the site of a wound in vivo in a mouse subcutaneous implantation model 3. Over 50 soluble growth factors and cytokine proteins have been identified in soluble extracts of dHACM,32, 33 suggesting that dHACM contains soluble components that elute from the tissue and stimulate the growth and chemotactic migration of different types of stem cells, thus amplifying the number of stem cells locally. However, due to the complexity of this unique material, a causative effect cannot be assigned to any single regulatory protein or other signaling molecule either currently identified or yet to be identified in dHACM tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The dHACM allografts have been utilized in the treatment of chronic wounds, such as diabetic foot ulcers and venous ulcers 29, 30, 31. Over 50 growth factors, cytokines, chemokines, and tissue inhibitors of metalloproteinases (TIMPs) have been previously identified in dHACM tissues,32, 33 many of which are known to stimulate paracrine responses in cells involved in healing and tissue repair, such as human dermal fibroblasts, microvascular endothelial cells, and stem cells. Previously published animal dermal wound models have shown that dHACM promotes the recruitment of both hematopoietic and mesenchymal stem cells to the treated site of injury 3.…”
Section: Introductionmentioning
confidence: 99%
“…Dehydrated human amnion/chorion membrane (dHACM) is a dehydrated human tissue allograft comprised of amnion and chorion membranes derived from donated human placentas. PURION ® processed dHACM (AmnioFix ® , MiMedx Group, Inc., Marietta, GA) has been shown to retain the growth factors in natural amniotic membrane including PDGF-AA, PDGF-BB, bFGF, TGF-β1, EGF, VEGF, and PlGF [14]. In addition to growth factors, cytokines including anti-inflammatory interleukins (IL-1ra, IL-4, and IL-10) and the TIMPs (TIMP-1, TIMP-2, and TIMP-4) which help regulate the matrix metalloproteinase (MMP) activity are also present in dHACM [14].…”
Section: Discussionmentioning
confidence: 99%
“…The amniotic membrane is isolated from the placenta and preserved with a proprietary PURION ® Process that involves gentle cleansing of the layers and dehydration of the tissue, resulting in an allograft with a 5-year shelf-life under ambient conditions (21). The growth factors and cytokines found to be present in dHACM induce human dermal fibroblast proliferation and angiogenesis, which are relevant to wound healing (22). Basic scientific studies of amniotic membrane using dHACM show the ability of the tissue to recruit multiple stem cells relevant to wound repair and regeneration (22).…”
Section: Discussionmentioning
confidence: 99%
“…The growth factors and cytokines found to be present in dHACM induce human dermal fibroblast proliferation and angiogenesis, which are relevant to wound healing (22). Basic scientific studies of amniotic membrane using dHACM show the ability of the tissue to recruit multiple stem cells relevant to wound repair and regeneration (22).…”
Section: Discussionmentioning
confidence: 99%